2019
DOI: 10.1002/bmc.4474
|View full text |Cite
|
Sign up to set email alerts
|

Extraction technology, component analysis, and in vitro antioxidant and antibacterial activities of total flavonoids and fatty acids from Tribulus terrestris L. fruits

Abstract: The current study focused on the extraction technology, components analysis, in vitro antioxidant and antibacterial activities of total flavonoids and fatty acids from Tribulus terrestris L. fruits. The extraction process of total flavonoids and fatty acids was optimized by the response surface method, and the compositions were identified from the two extracts by HPLC–DAD–ESI–MS− and GC–MS, respectively. In addition, the antioxidant and antibacterial activities were evaluated by assay of ABTS, DPPH radical sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…These results suggest that the antibacterial activity of TT is correlated mostly with the saponin content. Flavonoid fractions from TT leaves and fruits have also been proven to have antibacterial activity against E. coli, Salmonella, Staphylococcus aureus, and Streptococcus [39,40].…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…These results suggest that the antibacterial activity of TT is correlated mostly with the saponin content. Flavonoid fractions from TT leaves and fruits have also been proven to have antibacterial activity against E. coli, Salmonella, Staphylococcus aureus, and Streptococcus [39,40].…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…P. tomentosa has wide-ranging biological activities comprising antiviral, antioxidant and antibacterial effects [ 136 , 138 ]. It is mostly used for the treatment of various diseases, such as inflammatory bronchitis, upper respiratory tract infection, asthma, tonsillitis, gonorrhea, traumatic bleeding, enteritis, bacteriological diarrhea, erysipelas, swelling, bronchopneumonia, conjunctivitis, and hemorrhoids [ 139 , 265 ]. Furthermore, P. tomentosa has been known to have an antiviral effect on SARS-CoV PLpro.…”
Section: Known Medicinal Plants Acting On Ace-2 Receptormentioning
confidence: 99%
“…The antioxidant activities of the ethanol extract obtained from the fruit of the plant were found to have moderate DPPH (IC50: 11.52 µg /mL), ABTS (IC50: 6.74 µg /mL) radical scavenging and Brazilian Archives of Biology and Technology. Vol.64: e21210249, 2021 www.scielo.br/babt iron (III) ion reducing power activity (0.11 mmol Fe 2+ /100 µg/mL) compared to the standard [32]. In our present study, the DPPH radical scavenging activities of the aerial parts of the plant were examined and the IC50 values of the methanol extracts obtained by all three methods were found to be 0.277-0.372 mg/mL.…”
Section: Discussionmentioning
confidence: 59%
“…In another study, terrestrosin A-E, desgalactotigonin, F-gitonin, gitonin, desglucolanatigonin and (25R,S)-5α -spirostan-3βol -3 -O-β3-D-galactopyranosyl(1-2)-β-D-glucopyranosyl (1-4)-β-Dgalactopyranoside were isolated from an 80% ethanol extract prepared from the fruit of the plant [37]. It was determined by HPLC-DAD-ESI-MS that the ethanol extract obtained from the fruit of the plant contained quercetin 3,7 diglucoside+xyl, isomer of quercetin 3-O-arabinosyl galactoside, kaempferol-3-gentiobioside, isoquercitrin, astragaloside, sumaflavone, apigenin-6,8 glucoside+xyl, quercetin-3-gentiobioside [32]. According to our present knowledge, no studies have been reported regarding the effects of different extraction solvents/ methods on the chemical content of the plant.…”
Section: Discussionmentioning
confidence: 99%